Induction of Peripheral Tolerance in Ongoing Autoimmune Inflammation Requires Interleukin 27 Signaling in Dendritic Cells - Thomé, Rodolfo; Moore, Jason N.; Mari, Elisabeth R.; Rasouli, Javad; Hwang, Daniel; Yoshimura, Satoshi; Ciric, Bogoljub; Zhang, Guang-Xian; Rostami, Abdolmohamad M. (Frontiers in Immunology, 2017)
Peripheral tolerance to auto-antigens is induced via suppression of self-reactive lymphocytes, stimulation of tolerogenic dendritic cells (DCs) and regulatory T (Treg) cells. Interleukin (IL)-27 induces tolerogenic DCs and Treg cells; however, it is not known whether IL-27 is important for tolerance induction. We immunized wild-type (WT) and IL-27 receptor (WSX-1) knockout mice with MOG35-55 for induction of experimental autoimmune encephalomyelitis (EAE) and intravenously (i.v.) injected them with MOG35-55 after onset of disease to induce i.v. tolerance. I.v. administration of MOG35-55 reduced disease severity in WT mice, but was ineffective in Wsx-/- mice. IL-27 signaling in DCs was important for tolerance induction, whereas its signaling in T cells was not. Further mechanistic studies showed that IL-27-dependent tolerance relied on cooperation of distinct subsets of spleen DCs with the ability to induce T cell-derived IL-10 and IFN-γ. Overall, our data show that IL-27 is a key cytokine in antigen-induced peripheral tolerance and may provide basis for improvement of antigen-specific tolerance approaches in MS and other autoimmune diseases.